The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1039/d0sm01684e
|View full text |Cite
|
Sign up to set email alerts
|

Production of giant unilamellar vesicles and encapsulation of lyotropic nematic liquid crystals

Abstract: We describe a modified microfluidic method for making Giant Unilamellar Vesicles (GUVs) via water/octanol-lipid/water double emulsion droplets and encapsulation of nematic lyotropic liquid crystals (LNLCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…10,11,36 The oil phase containing a mixture of hexane and chloroform is incompatible with the PDMS chip, and our attempt to use n-octanol as the oil phase failed to generate liposomes, as it was recently shown that physical perturbation is needed to trigger dewetting for such a system. 11,38 Using a mixture of paraffin oil and n-hexanol (v/v% of 40 : 60), our results show that double emulsions with varying sizes can be stably produced, leading to liposome formation via spontaneous dewetting. At this stage, the detailed mechanism of how the mixture of paraffin oil and n-hexanol can trigger dewetting process is still unclear, as a more comprehensive analysis, such as comparing the interfacial tensions between three phases, is required to reveal it.…”
Section: Formation Of Double-emulsion Droplets and Liposomes With Hig...mentioning
confidence: 82%
“…10,11,36 The oil phase containing a mixture of hexane and chloroform is incompatible with the PDMS chip, and our attempt to use n-octanol as the oil phase failed to generate liposomes, as it was recently shown that physical perturbation is needed to trigger dewetting for such a system. 11,38 Using a mixture of paraffin oil and n-hexanol (v/v% of 40 : 60), our results show that double emulsions with varying sizes can be stably produced, leading to liposome formation via spontaneous dewetting. At this stage, the detailed mechanism of how the mixture of paraffin oil and n-hexanol can trigger dewetting process is still unclear, as a more comprehensive analysis, such as comparing the interfacial tensions between three phases, is required to reveal it.…”
Section: Formation Of Double-emulsion Droplets and Liposomes With Hig...mentioning
confidence: 82%
“…To verify the formation of lipid membranes, we encapsulated fluorescein and 0.2 M sucrose in the inner core of the double emulsions (along with 2% w/w PVA) prior to tip streaming as previously described. , The resulting droplets were collected in a 2% w/w PVA solution (blank) or in 2% w/w PVA solution containing 50 μg/mL α-hemolysin. The latter spontaneously incorporates into the phospholipid membrane, forming narrow pores.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning octanol de-wetting and separation on-chip demonstrated by Deshpande et al [86], LO phase concentration was adjusted to provide an appropriate interfacial tension that induces spontaneously de-wetting. This assures the separation of octanol residues from GUVs in a two-phase sedimentation process that takes about 1-2 h. This principle of separation by sedimentation is due to the octanol buoyancy that allows its precipitation for further supernatant extraction off-chip [87], which makes the proposed device a simpler low-cost alternative with high effectiveness for the synthesis of GUVs.…”
Section: Low-cost Octanol-assisted Liposomes Assemblymentioning
confidence: 99%